Identification of Clinical and Genomic Features Associated with SARS-CoV-2 Reinfections - Francisco Muñoz-López; Antoni E. Bordoy; Francesc Català-Moll; Verónica Saludes; David Panisello Yagüe; Mariona Parera; Ignacio Blanco; Pere-Joan Cardona; Cristina Casañ; Ana Blanco-Suárez; Sandra Franco; Álvaro F. García-Jiménez; et al. (Viruses, 2025)
Although SARS-CoV-2 reinfections remain a concern for healthcare systems worldwide, the factors driving them are still not fully understood. In this study, we examined data for 3303 individuals who experienced two SARS-CoV-2 infections between March 2020 and May 2022 from both clinical and viral genomics perspectives. Our findings indicate that viral evolution was the primary driver of reinfection. However, chronic conditions were common among reinfected individuals, including those under 26 years old, suggesting that the presence of underlying and/or chronic conditions increases susceptibility to reinfection. The median time elapsed between infections was one year, often coinciding with the emergence of new variants. While vaccination showed only a limited protective effect against reinfection, it drastically decreased the hospitalization rate, underscoring its role in mitigating disease severity. Our findings point to the need for more flexible vaccination strategies, especially for individuals with chronic conditions. Understanding the interactions between host factors and viral evolution is critical to strengthening prevention strategies and reducing the burden of reinfections and their possible long-term complications.